PENINGKATAN HASIL BELAJAR IPA KOMPETENSI DASAR SISTEM KOORDINASI DAN ALAT INDERA MANUSIA MELALUI METODE PEMBELAJARAN RESITASI PADA PESERTA DIDIK - Erlina Rosmaida Sitorus (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
AbstractThis study aims to determine the improvement of learning outcomes of basic science competency and Coordination System Tools Human Senses through recitation teaching methods. This study used a qualitative approach to obtain the data and analysis through reflection studies, participatory and collaborative. Development programs based data and information from students, teachers and classes are naturally social setting through two stages of action research cycles. Observations of student activity in cycle 1 average of 41.5% increased to 79% in cycle 2. Mastery learning materials also increased. It can be seen from the results of pre-cycle tests without learning recitation, the average value obtained by students in grade IX-2 is 69.40 rising to 74.58 in Cycle 1 with a passing grade and 44% in cycle 2 with a 88.19 percentage mastery learning reached 89% after recitation applied learning. It can be concluded that the activity and results of basic science learning competencies and Coordination System Tools Human senses in grade IX-2 SMP Negeri 131 Jakarta 1st semester of academic year 2013-2014 can be enhanced through learning methods recitation. Keywords: Science Learning Outcomes, Competencies, System Coordination, Learning Method